Independent and Cooperative Roles of Adaptor Molecules in Proximal Signaling during FcɛRI-Mediated Mast Cell Activation - Kambayashi, Taku (American Society for Microbiology (ASM), 2010)
Activation through FcɛRI, a high-affinity IgE-binding receptor, is critical for mast cell function during allergy. The formation of a multimolecular proximal signaling complex nucleated by the adaptor molecules SLP-76 and LAT1 is required for activation through this receptor. Based on previous T-cell studies, current dogma dictates that LAT1 is required for plasma membrane recruitment and function of SLP-76. Unexpectedly, we found that the recruitment and phosphorylation of SLP-76 were preserved in LAT1(−/−) mast cells and that SLP-76(−/−) and LAT1(−/−) mast cells harbored distinct functional and biochemical defects. The LAT1-like molecule LAT2 was responsible for the preserved membrane localization and phosphorylation of SLP-76 in LAT1(−/−) mast cells. Although LAT2 supported SLP-76 phosphorylation and recruitment to the plasma membrane, LAT2 only partially compensated for LAT1-mediated cell signaling due to its decreased ability to stabilize interactions with phospholipase Cγ (PLCγ). Comparison of SLP-76(−/−) LAT1(−/−) and SLP-76(−/−) mast cells revealed that some functions of LAT1 could occur independently of SLP-76. We propose that while SLP-76 and LAT1 depend on each other for many of their functions, LAT2/SLP-76 interactions and SLP-76-independent LAT1 functions also mediate a positive signaling pathway downstream of FcɛRI in mast cells.